Expanded renal lymphatics improve recovery following kidney injury. Issue 22 (21st November 2021) - Baranwal, Gaurav; Creed, Heidi A.; Black, Laurence M.; Auger, Alexa; Quach, Alexander M.; Vegiraju, Rahul; Eckenrode, Han E.; Agarwal, Anupam; Rutkowski, Joseph M.
Abstract: Acute kidney injury (AKI) is a major cause of patient mortality and a major risk multiplier for the progression to chronic kidney disease (CKD). The mechanism of the AKI to CKD transition is complex but is likely mediated by the extent and length of the inflammatory response following the initial injury. Lymphatic vessels help to maintain tissue homeostasis through fluid, macromolecule, and immune modulation. Increased lymphatic growth, or lymphangiogenesis, often occurs during inflammation and plays a role in acute and chronic disease processes. What roles renal lymphatics and lymphangiogenesis play in AKI recovery and CKD progression remains largely unknown. To determine if the increased lymphatic density is protective in the response to kidney injury, we utilized a transgenic mouse model with inducible, kidney‐specific overexpression of the lymphangiogenic protein vascular endothelial growth factor‐D to expand renal lymphatics. "KidVD" mouse kidneys were injured using inducible podocyte apoptosis and proteinuria (POD‐ATTAC) or bilateral ischemia reperfusion. In the acute injury phase of both models, KidVD mice demonstrated a similar loss of function measured by serum creatinine and glomerular filtration rate compared to their littermates. While the initial inflammatory response was similar, KidVD mice demonstrated a shift toward more CD4+ and fewer CD8+ T cells in the kidney. Reduced collagen deposition and improved functional recovery over time was also identified in KidVD mice. In KidVD‐POD‐ATTAC mice, an increased number of podocytes were counted at 28 days post‐injury. These data demonstrate that increased lymphatic density prior to injury alters the injury recovery response and affords protection from CKD progression. Abstract : Increased renal lymphatic density prior to kidney injury alters the inflammatory response. This appears to improve injury resolution beyond the acute phase, reducing fibrosis and the AKI to CKD progression.